Grabbing attention while reading website pages: the influence of verbal emotional cues in advertising - Ferreira, P. (2016)
The increasing use of the World Wide Web has promised a huge advertising platform for marketers. Investment in online advertising is growing and is expected to overcome traditional media. However, recent studies have reported that users avoid looking at advertising displayed on the World Wide Web. This study aimed at examining the impact of verbal emotional cues (negative/neutral/positive) to capture attention on website’s advertising areas through an eye tracker system. The results revealed significant statistical differences between fixations to negative, positive words and neutral words. Significant differences between the number of fixations and recognition of the target words were found only for the negative valence words. We conclude that negative emotional words could play a major role on user attention to advertising.